Effective management of femoral artery infection using lateral femoral bypass - Kotaro Mukasa, MD; Yasunori Yakita, MD, PhD; Ryosuke Marushima, MD; Musashi Tsuda, MD; Shinichiro Abe, MD, PhD; Soichi Asano, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
Infections of the groin present significant challenges for both infection control and limb salvage. This case report describes a patient with a history of penile cancer treated with radiation therapy, who developed a femoral artery infection following thromboendarterectomy. A lateral femoral bypass was performed, combined with thorough debridement and reconstruction using a rectus abdominis myocutaneous flap. This approach was effective for wound management, infection control, and revascularization. Although this procedure is rarely performed, it can serve as a valuable option for limb salvage in complex cases involving infection and previous radiation exposure.